The Influence of Final Project Product Development on Students’ Entrepreneurial Motivation - Murniati, Dewi Eka; Purwanti, Sutriyati; Handayani, Titin Hera Widi; Harsana, Minta; Abdul Razzaq, Abdul Rasid (Journal of Technical Education and Training, 2022)
While entrepreneurship education in the university gained its importance as an effort to develop the entrepreneurship of the younger generation, the majority of unemployed in Indonesia are undergraduate graduates. The students of the Culinary study program of Universitas Negeri Yogyakarta (UNY) are required to take the Final Project course in the form of Project-based learning. In this course, each student is given a project to develop a new food product innovation following the rules of Research and Development (R&D) steps with the 4 D method, namely define, design, develop, and disseminate. This product is expected to be a superior product for culinary students so that students can become entrepreneurs by making a real business venture after graduating. This study aims to: 1) examine the student's business orientation in the product development of the Final Project of Culinary, 2) investigate the entrepreneurial motivation of students, 3) determine the effect of student business orientation in the product development of the Final Project of Culinary on student entrepreneurial motivation. Survey research was employed in the study using quantitative descriptive methods and regression analysis to achieve the research objectives. The sample was calculated using the Slovin formula from a total population of 120 people in order to obtain a sample count of 103 people. The results show that: 1) the student's final project product development business orientation was in the good and moderate categories. The highest mean is obtained in the aspect of product formulas and ingredients for the product, while the lowest mean is obtained in the aspects of technology used for product manufacture, 2) the student entrepreneurial motivation is in the medium and high category in the general motivation aspect, while in the specific motivation aspect there are low, medium and high category results. The highest mean is in the need for achievement while the lowest mean is in the goal setting, 3) the final project product development has a positive and significant effect of 28% on students' entrepreneurial motivation. Suggestions based on the findings are also discussed.